ANALISIS PARTISIPASI MASYARAKAT DALAM MEMINIMALISIR DAMPAK PENGGUNAAN MEDIA SOSIAL PADA ANAK MELALUI OMAH BOCAH DI KOANG KECAMATAN JETIS KABUPATEN BANTUL YOGYAKARTA - Sofiana, Ade; Djannah, Sitti Nur (Jurnal Cakrawala Promkes, 2019)
Introduction: Social problems that have occurred have been successfully adopted by the development media that can be used as victims or perpetrators of crime through social media. The many negative impacts of using social media to make children, build the Omah Bocah community in the Koang area of Jetis District, Bantul Regency, Yogyakarta with the aim of minimizing the use of social media. The importance of integrating the community in the context of social issues so that it can be used to analyze the community in minimizing the use of social media use in children through Omah Bocah in Koang, Jetis District, Bantul Regency, Yogyakarta. Method: qualitative research with observational descriptive design. Using interview and observation methods. The research subjects consisted of eleven people consisting of one of the founders of Omah Bocah, two Omah Bocah administrators, three children of Omah Bocah users, two community leaders and three communities. Data collection tools are interview guides, observation guides, handpones and stationery. Results: Omah Bocah is a community that aims to minimize the impact of using social media. The history and strategy of the establishment of Omah Bocah with the role of community participation has included determining strategic locations and easy access. socialization of the delivery of vision and mission. Community empowerment and community self-reliance according to ability. Participation is seen from participation in planning, implementation, monitoring evaluation and utilization has been running well to include all levels of society with their respective roles. Obstacles from the implementation of Omah Bocah in the form of awareness from their children and also the ability to procure materials by the Omah Bocah management.